2018
DOI: 10.1002/cctc.201800411
|View full text |Cite
|
Sign up to set email alerts
|

Tin(IV) Sulfide Greatly Improves the Catalytic Performance of UiO‐66 for Carbon Dioxide Cycloaddition

Abstract: To overcome the limitations of metal-organicf rameworks (MOFs) for catalysis (e.g.,l ow catalytic activities resulting from blockageo ft he active metal centers by organic linkers) is of great importance.H erein, we demonstratet he formation of UiO-66 nanoparticles with ultrasmall size and linker defects with the aid of SnS 2 nanosheets.T he UiO-66 nanoparticles supported by SnS 2 nanosheets were found to exhibit excellent catalytic activity for the cycloaddition reactiono fC O 2 with propylene oxide under sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 39 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…Zhang's group showed that SnS 2 nanosheets were essential as UiO-66 support to inhibit the blockage of the active metal centers by organic linkers for cycloaddition of CO 2 with propylene oxide under solvent-free conditions. 322 323 This nanomaterial catalyzed the reaction of CO 2 addition with phenylacetylene yielding phenylpropiolate. In the presence of a base (Cs 2 CO 3 or K 2 CO 3 ), a TON value of 18 000 was obtained after 1 d at 50 °C in DMSO, which exceeded the performance of most reported catalysts, and this catalyst was reused 5 times.…”
Section: Cycloaddition Of Comentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang's group showed that SnS 2 nanosheets were essential as UiO-66 support to inhibit the blockage of the active metal centers by organic linkers for cycloaddition of CO 2 with propylene oxide under solvent-free conditions. 322 323 This nanomaterial catalyzed the reaction of CO 2 addition with phenylacetylene yielding phenylpropiolate. In the presence of a base (Cs 2 CO 3 or K 2 CO 3 ), a TON value of 18 000 was obtained after 1 d at 50 °C in DMSO, which exceeded the performance of most reported catalysts, and this catalyst was reused 5 times.…”
Section: Cycloaddition Of Comentioning
confidence: 99%
“…Zhang’s group showed that SnS 2 nanosheets were essential as UiO-66 support to inhibit the blockage of the active metal centers by organic linkers for cycloaddition of CO 2 with propylene oxide under solvent-free conditions . Indeed this catalyst was 11 times more active than the pure UiO-66 catalyst.…”
Section: Catalysis Of Organic Reactionsmentioning
confidence: 99%
“…According to the theoretical research and some previous reports, the probable catalytic mechanism of this CO 2 cycloaddition reaction is deduced and provided in Scheme . In this catalytic reaction, the open metal sites can be considered as the Lewis acidic sites to directly coordinate with the O atoms in epoxides first, leading to the activation of the epoxy rings.…”
Section: Resultsmentioning
confidence: 87%
“…Owing to their permanent porosity, large specific surface area and strong emissions, this class of materials have been widely used in the sensing field, such as metal ions [ 17 , 18 ], volatile organic compounds [ 19 ], and anions [ 20 , 21 ] or as a temperature sensor [ 22 ]. Among them, UiO-66 has emerged as a novel fluorescent sensor with ultra-high chemical stability, thermodynamic stability and good biocompatibility [ 23 , 24 ]. However, the unsatisfactory luminescence properties limit its further application in the field of fluorescence.…”
Section: Introductionmentioning
confidence: 99%